PERBEDAAN AKTIVITAS FISIK ANTARA WEEKDAY DENGAN WEEKEND PERSONIL TNI-AD PADA ERA PANDEMI COVID-19 - Rivaldi Ilman Syaputera, - (2021)
Physical activity in the era of the Covid-19 pandemic may change from usual due to the imposition of space restrictions in order to reduce crowds for workers, both public and private employees. This can lead to a decline in the health of workers, including TNI personnel. Therefore, researchers have the aim of testing whether there are differences in the physical activity of TNI personnel on weekdays or weekdays and on holidays or weekends during the Covid-19 pandemic era. The sample in this study is the personnel of the Dinas Jasmani TNI Angkatan Darat (AD) with a total sample of 39. This study uses an instrument in the form of an actigraph accelerometer which is used by each sample for 7 days (1 week) and hypothesis testing using the MannWhitney U test with degrees of freedom (sig. 0.05). The results of the study is the pattern of physical activity in the TNI AD Physical Service Personnel on weekdays is classified as heavy with an average energy expended of 10.08 kcal/minute, while on weekends it is classified as moderate activity with an average energy expended of 5.33 kcal/minute. Futhermore, in this research indicate that there is a significant difference between the physical activity of the Dinas Jasmani TNI AD personnel on weekdays weekends based on MVPAs during the Covid-19 pandemic era, where the physical activity carried out on weekdays is more than that carried out on holidays.